Crowdsourcing: A novel tool to elicit the student voice in the curriculum design process for an undergraduate diagnostic radiography degree programme. (October 2020) - St. John-Matthews, J.; Robinson, L.; Martin, F.; Newton, P.M.; Grant, A.J.
Abstract: Introduction: Stakeholder participation in healthcare curriculum design is an important aspect of higher education with stakeholders including students, staff members, clinical partners, healthcare organisations, patients and members of the public. Significantly, student co-creation, of the curriculum, has become increasingly important. Yet there is limited research which addresses how to engage this group in design processes. Methods: This paper represents the first phase of a three stage action research spiral whereby the authors evaluated the use of a novel tool for curriculum design processes, anonymised crowdsourcing. This initial phase was open to all students enrolled on an undergraduate diagnostic radiography programme in the UK. To confirm the reliability of the crowdsource design an established eight point crowdsourcing verification tool was applied. Results: Twenty-three unique ideas were generated by participants, 40 comments made and 173 votes cast. Inductive analysis of the comments generated five themes. These included: the role of technology enhanced learning; simulation activities; patient focused curriculum; mental wealth (resilience) authentic assessment approaches. An evaluation of those who had and had not engaged highlighted areas of improvement for the administration of the second and third iterations which will include a wider pool of participants. Conclusion: This study from a single programme offers lessons for others wishing to adopt and develop this approach elsewhere. Implications for practice: Several ideas elicited by the crowdsource have been considered by the curriculum design team and will be implemented in the 2020 curriculum thus demonstrating the impact on local education practice of this research approach.